2012
DOI: 10.1021/bm301166s
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cationic Nanogels for Nucleic Acid Delivery

Abstract: Cationic nanogels with site-selected functionality were designed for the delivery of nucleic acid payloads targeting numerous therapeutic applications. Functional cationic nanogels containing quaternized 2-(dimethylamino)ethyl methacrylate and a cross-linker with reducible disulfide moieties (qNG) were prepared by activators generated by electron transfer (AGET) atom transfer radical polymerization (ATRP) in an inverse miniemulsion. Polyplex formation between the qNG and nucleic acid exemplified by plasmid DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…The nanogels were purified using dialysis and characterized using dynamic light scattering and zeta potential analysis. Further details on nanogel synthesis and characterization can be found in Averick et al [6].…”
Section: Nanogel Synthesismentioning
confidence: 99%
“…The nanogels were purified using dialysis and characterized using dynamic light scattering and zeta potential analysis. Further details on nanogel synthesis and characterization can be found in Averick et al [6].…”
Section: Nanogel Synthesismentioning
confidence: 99%
“…In the former case, polymers grown from nanoparticles or flat surfaces, dramatically change particles stability, dispersibility and thermomechanical properties, in addition to tremendously enhancing lubricity, antifouling or antibacterial properties (53)(54)(55)(56)(57)(58)(59)(60)(61). Hybrids with proteins or nucleic acids increase stability of proteins in harsh environments, (including temperature, pH, and salts) assist in delivery of genes, and can be used in advanced drug delivery (45,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Figure 1 Results Of Scifinder Search On Various Crp Systemsmentioning
confidence: 99%
“…Further details on nanogel NSP synthesis and characterization can be found in the following reference. 19 …”
Section: Methodsmentioning
confidence: 99%
“…16–18 We have produced cationic nanogel nanostructured polymers (nanogel NSPs) by atom transfer radical polymerization (ATRP) to produce a bioresponsive, interconnected polymeric network for siRNA delivery. 19 This effort integrates several strategies for efficient siRNA delivery, including PEGylation, steric shielding of siRNAs, built-in features for endosomal escape, and stimuli-specific degradation mechanisms. We previously reported that nanogel NSPs demonstrate minimal dose-dependent cytotoxicity, efficient siRNA binding and release, and internalization into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%